INFLUENCE OF CORPORATE GOVERNANCE ON COMPANY VALUE WITH STOCK RETURN AND FINANCIAL PERFORMANCE AS A MEDIATOR VARIABLE - Pornpawee Worasatepongsa; Suchart Prakthayanon (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research was aimed at testing the influence of corporate governance on company value through the variable of stock return and financial performance. Data were collected from 50 stocks of companies registered in the Stock Exchange of Thailand (SET50 Index) in 2019. These stocks have good and secure business bases, high trading liquidity, large market capitalization and regular dividend payouts along with good-excellent governance scores from the Corporate Governance Report 2019 of Thailand. Based on the findings of this examination, it was concluded that corporate governance has negative direct effects on company value and corporate governance has a negative indirect influence through stock returns. However, company value is directly and positively influenced by financial performance. Oddly, this study did not find a direct or reverse correlation between stock return and financial performance in stocks.